Quantitative analysis of tumor-associated tissue eosinophilia in different histological grades of oral squamous cell carcinoma - Rashmi Bankur; Charlotte Rodrigues; D Anjaly; Pillai Arun Gopinathan; Praveen Kumar Bankur (Wolters Kluwer Medknow Publications, 2016)
Background and Objectives: Oral squamous cell carcinoma (OSCC) is the 8 th most common aggressive epithelial malignant neoplasm worldwide today. The eosinophil may be a "multifaceted cell" that can be associated with wound-healing processes, as well as to tissue damage which has increased the speculations around tumor-associated tissue eosinophilia in malignant tumors. The aim of this study was to detect the role and quantitative analysis of tumor-associated tissue eosinophils in different histological grades of OSCC. Materials and Methods: A retrospective study was carried out in sixty cases of histopathologically graded OSCCs. Tissue sections of 4 μ thickness were made from paraffin-embedded tissue blocks and were stained with hematoxylin and eosin. Eosinophils were counted under randomly selected twenty high-power (×40) fields. Data were subjected to statistical analysis using ANOVA test. Results: Higher mean eosinophils were recorded in well-differentiated squamous cell carcinoma (WDSCC) followed by moderately differentiated squamous cell carcinoma (MDSCC) and poorly differentiated squamous cell carcinoma (PDSCC) groups, respectively. The difference in mean eosinophils was found to be statistically significant between WDSCC and MDSCC (P < 0.001), as well as between WDSCC and PDSCC (P < 0.001). Conclusion: Tumor-associated tissue eosinophil count is higher in WDSCC as compared to moderate and PDSCC.